2021
DOI: 10.3389/fcell.2021.693342
|View full text |Cite
|
Sign up to set email alerts
|

TREM2, Driving the Microglial Polarization, Has a TLR4 Sensitivity Profile After Subarachnoid Hemorrhage

Abstract: Increasing evidence suggests that triggering receptor expressed on myeloid cells 2 (TREM2) is implicated in the pathophysiology of neuroinflammation. The aim here was to investigate the neuroprotective role of TREM2 and its regulatory mechanism after subarachnoid hemorrhage (SAH). TREM2 siRNA was administered to measure the detrimental role of TREM2 in mediating microglial polarization in vivo and in vitro after experimental SAH. The relationship between Toll-like receptor 4 (TLR4) signaling and TREM2 was furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…TREM2 also modulates microglial function in disease states, and several studies demonstrated that TREM2 deficiency impairs the clearance of apoptotic neurons and pathological substrates, thus attenuating disease progression [197,327,390]. TREM2 inhibition promotes pro-inflammatory microglial response and neurological deficit in a HS model [393]. Microglial TREM2 is also strongly implicated in AD pathology, and loss of its expression alters microglial phagocytosis responses, which contribute to the formation of dispersed Aβ plaques associated with increased neurotic damage [201].…”
Section: Triggering Receptors Expressed On Myeloid Cells 2 (Trem2)mentioning
confidence: 99%
“…TREM2 also modulates microglial function in disease states, and several studies demonstrated that TREM2 deficiency impairs the clearance of apoptotic neurons and pathological substrates, thus attenuating disease progression [197,327,390]. TREM2 inhibition promotes pro-inflammatory microglial response and neurological deficit in a HS model [393]. Microglial TREM2 is also strongly implicated in AD pathology, and loss of its expression alters microglial phagocytosis responses, which contribute to the formation of dispersed Aβ plaques associated with increased neurotic damage [201].…”
Section: Triggering Receptors Expressed On Myeloid Cells 2 (Trem2)mentioning
confidence: 99%
“…Neuroinflammation in post-SAH neuronal damage may be involved, given that heme and methemoglobin can act as toll-like receptor 4 (TLR4) agonists, as our lab and others have shown in hemorrhagic stroke [7][8][9]. Although TLR4 has a role in post-SAH inflammation [10,11], the connection to cognitive dysfunction and the specific glia involved in post-SAH neuronal injury have yet to be determined. Our lab and others have previously shown that microglia have a critical role in mediating neuronal injury after SAH [12], but conditional knockouts of TLR4 on individual glial populations have never been performed.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, TREM2 is a key component of the microglial response and activation and is essential for their metabolism to detect and respond to neurodegenerative cues and it is involved in numerous pathways such as cell survival and homeostasis [ 23 , 37 ]. Studies have also shown that a mutation or a decrease in TREM2 expression is associated with a downregulation of CD68 [ 38 , 39 ], whereas TREM2 overexpression triggers Arg-1 expression [ 40 ].…”
Section: Discussionmentioning
confidence: 99%